Mechanical properties of unsaturated polyester composites reinforced with acid-treated palm kernel shell at various filler loadings - Samsudin, Dalina; Abdul Wahab, Nor Mazlina; Zakaria, Salamiah; Hashim, Faiezah; Ahmad, Zuliahani; Syed Ismail, Sharifah Nafisah; Mustafa, Mohamad Syamaizar (Universiti Teknologi MARA, Perlis, 2025)
An attempt has been successfully made to utilize palm kernel shell waste as a potential filler in unsaturated polyester composites. A problem with the hydrophilic characteristics of palm kernel shell, which restricts its compatibility and interfacial bonding with polyester matrix, was overcome by chemical treatment with acrylic acid. The composites were prepared via the hand lay-up technique with different amounts of filler loadings (0, 15, 30, 45, and 60 php). Esterification of cellulosic palm kernel shell fiber by acrylic acid has increased the surface roughness of the fibers which tended to improve the mechanical interlocking between the fiber and matrix interphase. The effects of acid treatment and filler loading on the mechanical and morphological properties of composites were studied using mechanical and morphological tests. The addition of palm kernel shell showed a decrement in strength compared with pristine samples due to poor interaction and compatibility of constituent materials. The modulus for tensile and flexural was gradually increased from 2.4 GPa to 2.9 GPa and 2.8 GPa to 3.5 GPa, respectively, through an increase in filler loadings. These results reflect increased stiffness of the composites imparted by the stiff filler. Nevertheless, 15 php of palm kernel shell treated with acrylic acid yielded improved tensile and flexural strength at 32 MPa and 49 MPa, respectively. This result is due to the increased interfacial adhesion between filler and matrix, as exhibited in the Scanning Electron Microscope micrograph, which showed better interfacial interaction within the composites.